Features of accounting of virtual currency (cryptocurrency) as a component of virtual assets of Ukraine - Syrtseva, S.V.; Luhova, O.I. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2021)
In the course of the research it was established that according to the Ukrainian legislation the virtual currency (cryptocurrencies) is an unsecured virtual asset. The accounting of such assets is not regulated by the National Accounting Standards, as in Ukraine entities cannot officially own them due to the lack of legal status. At the international level, virtual currency is accounted for using International Financial Reporting Standards (cryptocurrencies retained as intangible assets in accordance with IAS 38 “Intangible Assets”; cryptocurrencies held for sale are recognized as inventories in accordance with IAS 2 “Inventories”). It is established that the virtual currency (cryptocurrencies) in most cases is held for the purpose of obtaining investment income from resale, the main option of accounting for cryptocurrencies should be part of inventories.
Keywords: virtual asset; virtual currency; inventories; cryptocurrencies; accounting; intangible assets